Microcomputer application for instrumentation development in drip irrigation system - Mohd. Hudzari, Razali; Mohd Noorman, Masrek; Syazili, Roslan (2013)
Drip irrigation is the most water efficient system available to water garden. Some systems are so efficient that they only allow a few liters of water per hour to fall into the soil and the best way to water the plants at ground level where they need it the most. Installing an irrigation system such as sprinkler or drip system without automation has always been a difficult and frustrating problem for homeowners, contractors and growers alike. An ideal choice would be to use an irrigation controller, which can be the greatest help in conserving water and time. With the right controller, the right amount of water will be able to apply, at the right time, for optimum plant growth. In this study, the amounts of water that produce from microcontrollers and from different water pumps are measure. The result show the average water produced is similar. Microcomputer or controller can manage the flow of water through the irrigation system. Simple controllers such as a mechanical tap timer only need to you set the watering time required. More complex controllers are capable of watering different garden zones at different times and even on different days. It is an essential tool to apply water in the necessary quantity and at the right time to sustain agricultural production and to achieve high levels of efficiency in water, energy and chemical uses